1964
DOI: 10.1021/ja01058a051
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of Azomethane

Abstract: COMMUNICATIONS TO THE EDITOR745 I For the ethyl radical, B has a value of 58.5 gauss.' Solution of the equations, aaxia1.H = Bp COS2 eaxial, Uequat-H = Bp COS2 eequat, and Oequat-H = Baxial-H f 120' (tetrahedral a-carbon atom) gives the results listed in Table I. 6 It is interesting that the value of Oaxial for the a-hydrogens of the 4-t-butylcyclohexane-1,2-dione radical-anion is the same as found for cyclohexene by n . m .~-.~ Our results demonstrate the application of e.s.r. to conformational analysis of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 2 publications
5
20
0
Order By: Relevance
“…25,26 QM(GVB-CAS)/MM dynamics on trans-azomethane revealed that the decay lifetimes, associated with the torsion around the central double bond, are mainly influenced by mechanical restrictions from interactions with the solvent, and do not depend on the polarity, with similar decay times in polar and non-polar solvents. 161 Furthermore, these simulations also confirmed the absence of dissociation processes in solution, in agreement with experimental results 171 and other dynamic studies. 172 Surface hopping SA-CASSCF(10,8)/MM simulations have been performed on 9H-hypoxanthine and its methylated derivative (9M-hypoxanthine) in the gas phase and water.…”
Section: In Watersupporting
confidence: 87%
“…25,26 QM(GVB-CAS)/MM dynamics on trans-azomethane revealed that the decay lifetimes, associated with the torsion around the central double bond, are mainly influenced by mechanical restrictions from interactions with the solvent, and do not depend on the polarity, with similar decay times in polar and non-polar solvents. 161 Furthermore, these simulations also confirmed the absence of dissociation processes in solution, in agreement with experimental results 171 and other dynamic studies. 172 Surface hopping SA-CASSCF(10,8)/MM simulations have been performed on 9H-hypoxanthine and its methylated derivative (9M-hypoxanthine) in the gas phase and water.…”
Section: In Watersupporting
confidence: 87%
“…Configurational isomers of acyclic analogs azoisobutane (ArcH,(transcis) = 0.33 ppm (CH30D))34 and azoisopropane (15) ( A~~~~( t r a n s -c i s ) = 0.14 ppm, ArcH(trans-cis) = 0.49 ppm (CCL))15 behave likewise while the parent, azomethane (ArcH,(trans-cis) = -0.10 ppm (DzO)), 35 falls outside the pattern. Configurational isomers of acyclic analogs azoisobutane (ArcH,(transcis) = 0.33 ppm (CH30D))34 and azoisopropane (15) ( A~~~~( t r a n s -c i s ) = 0.14 ppm, ArcH(trans-cis) = 0.49 ppm (CCL))15 behave likewise while the parent, azomethane (ArcH,(trans-cis) = -0.10 ppm (DzO)), 35 falls outside the pattern.…”
Section: Nmr Spectramentioning
confidence: 99%
“…spectra and comparison with the spectra of some model compounds. The pyrazole (7) is characterised by the resonance of the 5-methyl at r 7.48, shielded by the anisotropic effect of the carbonyl group relative to the resonance of the 3-methyl at r 7.78. To facilitate comparisons and avoid complications of possible changes in preferred conformations a further model compound, the bicyclic pyrazole ( 8), was prepared by reaction of hydrazine with 2-acetylcyclohexanone and subsequent acetylation with acetic anhydride in pyridine.…”
Section: (131mentioning
confidence: 99%
“…105-106 "C (lit., m.p. 106 oC).8 Acetylation by Method A afforded a yellow oil, which on distillation gave as a colourless oil 1-acetyl-3,5dimethyl-lH-pyrazole (7) 5,6, .-A solution of 2-acetylcyclohexanone (1 .O g) and hydrazine hydrate (0.4 ml) in ethanol (20 ml) was stirred at room temperature for 30 min. Concentration under reduced pressure afforded a yellow oil (1.1 g) which was acetylated by Method A at room temperature for 16 h. Concentration under reduced pressure afforded a yellow oil (1.25 g) which was purified by bulb-to-bulb distillation (100 "Cl0.1 mmHg) to give initially a colourless oil which slowly solidified.…”
Section: 7-diacetyl-l3a4788a-hexuhydro-35-dimethylbenzo-mentioning
confidence: 99%